A voyage from Apollonian Munich to Dionysian Venice in Thomas Mann's Death in Venice - Ayyildiz, Nilay Erdem (Sciendo, 2019)
This paper explores the intersection of cities and the protagonist's Apollonian-Dionysian dichotomy in Thomas Mann's preeminent semi-autobiographical novella Death in Venice (1912) within the cultural and contextual considerations of 20th-century Munich and Venice. The protagonist Gustav von Aschenbach's oscillation between artistic appreciation and sensual desire is personified by the contrasts Munich draws as a city of enlightenment against Venice which is the city of sensuality and freedom. The article indicates that the narrator associates Nietzsche's conceptions of the Apollonian and Dionysian parts of human nature with Venice, which acts as a character providing crucial elucidation in regards to the mental state of the protagonist throughout the novella. Thus, the study sheds light upon the symbolic voyage Aschenbach embarks upon - from Apollonian nature to Dionysian nature; from Munich to Venice, where his predominating Dionysian nature burst out through the city, luring him to his own demise. © 2019 Nilay Erdem Ayylldlz, published by Sciendo 2019 Bloom, H. 2003.